Wilson's Disease in Finland: A Nationwide Population‐Based Study - Jussi O.T. Sipilä; Marja Hietala; Ville Kytö; Valtteri Kaasinen (WILEY, 2025)
Background
Data on the epidemiology and prognosis of Wilson's disease are scarce, and no clinical data are available from Finland. Methods
All persons diagnosed and treated for Wilson's disease in Finnish hospitals in 1998 to 2017 were identified. Data were collected from national registries and patient charts.
Results
The point prevalence was 0.45/100,000 (95% confidence interval, 0.29-0.67) on December 31, 2017, but no more than 0.35/100,000 (95% confidence interval, 0.21-0.55) among native Finns. Annual incidence was 0.016/100,000 (95% confidence interval, 0.0093-0.026). Median age at diagnosis was 15.8 years (interquartile range, 8.3-32.2; range, 3.8-48.1 years). Upon presentation, liver damage was observed in 58%, neurological signs and symptoms (most often tremor and dysarthria) in 40%, and 32% of patients were asymptomatic. Patients had poorer long-term survival (hazard ratio, 2.92 for death;P= 0.005) compared with matched controls.
Conclusions
Wilson's disease is very rare in Finland. Patients have an increased risk of death indicating an unmet treatment need.